Spiritual Ideology Of Moral Leadership In Santi Parwa - Ida Ayu Komang Arniati; Ida Ayu Surya Wahyuni; Ida Ayu Putu Sari (Jurnal Penelitian Agama Hindu, 2020)
This research aims to uncover, understand, and deeply describethe moral spiritual leadership of Santi Parwa, as a reference and guide for Hindus in understanding discourse and ideology as a leader based on moral spirituals. The idealism ofpemi kIran research aims to establish and communicate that literary works can be a social, political and cultural force, with a message can give pencerahan positive presiation enlightenment for Hindus to understand the moral spiritual ideology of Santi Parwa's leadership. This type of descriptive research means analysis in the form of santi parwa documents, and the data is a description of written words. Data sources from Santi Parwa books and scientific works in the form of research, journals and other supporting books. The data analysis method used in this study is a hermeneutic method, focusing on Santi Parwa relating to symbols, languages, discourses, which is open to interpretation according to its context with an interpretive approach that is a reader whombaca usesexisting knowledge, ideas, and concepts to reflect and can produce a description of the Spiritual Ideology of Moral Leadership in Santi Parwa wacana. The results of thestudy, First, wacana spiritual moral leadership in Santi Parwa background in the form of wacana in the form of writings, wordsor ucapan that are contextual. The Moral Spiritual Discourse of Leadership in Santi Parwa consists of: (1) Peace of Mind, (2) Obligation;; (3) Kepercayaan diriConfidence; (4) Justice; (5) Cooperation Kerjasama. Second, the ideology behind spiritual moral leadership in Santi Parwa is Ideology that formulates thewhole system ofthinking, value, and basic attitudes that undercut the story of Santi Parwa, which consists of: (1) dharma deology; (2) Ideology of duty; (3) Ideology of Bahkti.